2018
DOI: 10.1038/s41467-018-07318-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow of cerebrospinal fluid is driven by arterial pulsations and is reduced in hypertension

Abstract: Flow of cerebrospinal fluid (CSF) through perivascular spaces (PVSs) in the brain is important for clearance of metabolic waste. Arterial pulsations are thought to drive flow, but this has never been quantitatively shown. We used particle tracking to quantify CSF flow velocities in PVSs of live mice. CSF flow is pulsatile and driven primarily by the cardiac cycle. The speed of the arterial wall matches that of the CSF, suggesting arterial wall motion is the principal driving mechanism, via a process known as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

81
1,079
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 712 publications
(1,241 citation statements)
references
References 39 publications
81
1,079
9
1
Order By: Relevance
“…The maximal recorded PVS velocity (not including model 6) was computed to be 5.66 µm/s in model 4. In the experimental studies, several investigators used an infusion rate of 2 µL/min in rodents [30,31,46], which was shown to increase ICP by 2.5 mmHg [31], a substantial increase, but less than in our model of a human with an infusion rate of 1.5 mL/min. In addition, Bedussi et al [5], used a much lower infusion rate of 0.34 µL/min, only resulting in a pressure rise of 0.1 mmHg.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The maximal recorded PVS velocity (not including model 6) was computed to be 5.66 µm/s in model 4. In the experimental studies, several investigators used an infusion rate of 2 µL/min in rodents [30,31,46], which was shown to increase ICP by 2.5 mmHg [31], a substantial increase, but less than in our model of a human with an infusion rate of 1.5 mL/min. In addition, Bedussi et al [5], used a much lower infusion rate of 0.34 µL/min, only resulting in a pressure rise of 0.1 mmHg.…”
Section: Discussionmentioning
confidence: 70%
“…Mestre et al [46] demonstrate PVS collapse after fixation. This observation entails that a gap size of 100 nm at the precapillary level, as used by Faghih and Sharp [19] and measured after fixation, may be an underestimation.…”
Section: Extended Capillary Gaps (Model 6)mentioning
confidence: 97%
See 2 more Smart Citations
“…However, there is still some controversy about the “glymphatic” function . The perivascular spaces (PVS), as the main component of glymphatic system, carry CSF through the brain, sweeping away metabolic waste . After being directly administrated into the CSF compartment, molecular imaging probes or contrast agents could move along the flow of CSF, and transport from the subarachnoid space entering the brain parenchyma via the PVS .…”
Section: Introductionmentioning
confidence: 99%